Tailored treatments in inborn errors of immunity associated with atopy (IEIs-A) with skin involvement - Giancotta, Carmela; Colantoni, Nicole; Pacillo, Lucia; Santilli, Veronica; Amodio, Donato; Manno, Emma Concetta; Cotugno, Nicola; Rotulo, Gioacchino Andrea; Rivalta, Beatrice; Finocchi, Andrea; Cancrini, Caterina; Diociaiuti, Andrea; et al. (Frontiers in Pediatrics, 2023)
Inborn errors of immunity associated with atopy (IEIs-A) are a group of inherited monogenic disorders that occur with immune dysregulation and frequent skin involvement. Several pathways are involved in the pathogenesis of these conditions, including immune system defects, alterations of skin barrier and metabolism perturbations. Current technological improvements and the higher accessibility to genetic testing, recently allowed the identification of novel molecular pathways involved in IEIs-A, also informing on potential tailored therapeutic strategies. Compared to other systemic therapy for skin diseases, biologics have the less toxic and the best tolerated profile in the setting of immune dysregulation. Here, we review IEIs-A with skin involvement focusing on the tailored therapeutic approach according to their pathogenetic mechanism.